Unveiling the Urban Mosaic of Metro Vancouver: Shaping a New Urban Identity - Li, Jiangnan (Transactions on Environment, Energy and Earth Sciences, 2024)
Vancouver has always had an open and tolerant social attitude and multiculturalism as part of the city's identity, which has attracted many immigrants. The city in modern society is complex, gathering people with different occupations, personalities and identities, and their distribution in space also has differentiated clusters. This paper shares findings from researching the different characteristics of people in different sub-divisions of the metro Vancouver area, and uses Urban Mosaic maps to present them. This paper aims to provide a more intuitive data visualization to show the differences between urban identity and regional development of people in a city, and to provide a possibility to serve the future planning and policy making of the city.